Ventanillas de Salud: A Collaborative and Binational Health Access and Preventive Care Program - Rangel Gomez, Maria Gudelia; Tonda, Josana; Zapata, G. Rogelio; Flynn, Michael; Gany, Francesca; Lara, Juanita; Shapiro, Ilan; Rosales, Cecilia Ballesteros (Frontiers in Public Health, 2017)
Abstract (Word count: 122/ Character count: 848) While individuals of Mexican origin are the largest immigrant group living in the U.S., this population is also the highest uninsured. Health disparities related to access to healthcare, among other social determinants, continue to be a challenge for this population. The government of Mexico, in an effort to address these disparities and improve the quality of life of citizens living abroad, has partnered with governmental and non-governmental healthcare organizations in the U.S. by developing and implementing an initiative known as Ventanillas de Salud—Health Windows—(VDS). The VDS are located throughout the Mexican Consular network and aim to increase access to healthcare and health literacy, provide health screenings, and promote healthy lifestyle choices among low-income and immigrant Mexican populations in the U.S.